Effect of Water Temperature to Survival and Development of Larvae of Two Local Aedes Aegypti Strains - Ramadhani Eka Putra; Gunadi Trinuroni (Jurnal Biodjati, 2019)
Global warming has been reported in last decades. Chang-es in average Earth’s temperature may affect the physiology of many insect species, especially the ones which act as a human disease vec-tor, like Aedes aegypti. In this study, the effect of increasing water temperature on physiological components related to development period, sex ratio, and body size of two distinctively strains, VCRU (Vector Control Research Unit) and Pangandaran. Thirty larvae of each strain kept inside distilled water with the temperature of 25°C, 27°C, 30°C, 33°C, 35°C, 40°C which replicated three times. Observa-tions were conducted until all larvae metamorphed into adults or all larvae dead. Development rate and time were analyzed by frequency dependent mean. The result showed that the optimum temperature for larvae development of VCRU strain was 27-30°C with a survival rate of 84% while it was 30°C for Pangandaran strain, with the surviv-al rate of 83%. Larvae of both strains showed 100% mortality rate when kept inside a container with water temperature exceed 33°C. Both strains showed the highest and the lowest male:female ratio at similar water temperature which were 33°C and 30°C, respec-tivelly. Highest and lowest ratio of VCRU was 1.25 and 0.6, respec-tively, while it was 1.4 and 0.6 for Pangandaran. In general, larvae lived in increasing water temperature showed reducing wing width.